“Do it all but don’t kill us”: (Re)positioning teacher educators and preservice teachers amidst edTPA and the teacher strike in West Virginia - Sherfinski, Melissa; Hayes, Sharon; Zhang, Jing; Jalalifard, Mariam (Education Policy Analysis Archives, 2019)
We explore how two “happenings” representing different political, social, historical and economic influences converge to shape the narratives of preservice teachers and teacher educators in West Virginia. These happenings are the 2017-2018 edTPA roll out and the teacher strike of February 2018. We use the framework of sensemaking to explore preservice teacher and teacher educator identity/agency using a phenomenological analysis of narratives accessed through narrative portfolios, artifacts, and interviews with pre-service teachers, mentors (supervising teachers), and teacher educators. We found that the confluence of these political moments reinforced a neoliberal orientation for both preservice teachers and teacher educators, positioning preservice teachers to expect teacher educators to intensively support the edTPA and ensure their success while silencing the collective history and moral imperative of protest. Preservice teachers and some mentors reframed the edTPA as a pathway to increased teacher pay/meritocracy by linking it with the National Boards, yet there were pockets of resistance within this among both preservice teachers and teacher educators. These findings are important for informing educational policy and practice around both corporate involvement in assessment/accountability policy and preservice teachers’ and teacher educators’ roles in protest at this moment when both are expanding simultaneously.